TEKANAN EKSTERNAL, KETIDAKPASTIAN LINGKUNGAN, KOMITMEN MANAJEMEN DAN KUALITAS APARAT KAMPUNG TERHADAP PENERAPAN TRANSPARANSI PELAPORAN KEUANGAN (Studi Kasus Pemerintahan Kampung Di Kabupaten Boven Digoel) - arius kambu (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2019)
The aim of the study was to describe and describe aspects of external pressure, environmental uncertainty, management commitment and the overall quality of village government apparatus in relation to the transparency of village financial reporting. This research is a qualitative research with a case study approach and data collection techniques through field observations, interviews, document review and literature studies and empirical studies. Informants in this study were village officials and community leaders. The findings of the study on financial reporting transparency found external pressure variables, environmental uncertainty, management commitment and the quality of village apparatus were still the inhibiting variables in voicing the principles of transparency in village financial reporting. Whereas there are other reasons that the suitability of village financial management is based on Law Number 33 of 2004.